AGREEMENT ON THE SALE AND PURCHASE OF HOUSES TO BE BUILT IN CONJUNCTION WITH THE CONSUMER PROTECTION ACT - Ahmad Fauzi Fauzi; Surya Perdana Perdana; Mukhlis Ibrahim Ibrahim (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
In residential buying agreements, contracts governing default are usually common. Default is stated by expressing negligence in two respects, whether it is negligence in payment of instalment or negligence in the delay of settlement of house construction which will be delivered to the consumer. The developer's responsibility is usually related to the delay of the house construction and delivery to the consumer. In the execution of the sale and purchase transaction of the house to be built, consumers rarely gain consumer protection rights as regulated and mentioned in the article on consumer rights and business actor obligations contained in Article 4 and 7 of Law no. 8 of 1999 on Consumer Protection. Furthermore, field practice reality shows that consumers and developers do not have the same bargaining position, where the consumer are usually required to follow the agreement that has been standardized by developers who are legally contrary to Article 18 of Law no. 8 of 1999 on Consumer Protection.